Minimal Thermal Requirements for Development and Activity of Stored Product and Food Industry Pests (Acari, Coleoptera, Lepidoptera, Psocoptera, Diptera and Blattodea): A Review - Stejskal, Vaclav; Vendl, Tomas; Li, Zhiong; Aulicky, Radek (Insects, 2019)
Low temperatures play an important role in arthropods because they affect both the individual and population development of all physiological and behavioural activities. Manipulation with low temperatures is a primary nonchemical pest control method. For stored product and food industry practitioners, a knowledge of pest thermal requirements, in particular threshold temperatures at which development and other activities of a particular pest species cease, is of crucial importance. This review presents summary data regarding the lower temperature thresholds of 121 species of stored product and food industry pests from six arthropod taxa (Acari, Coleoptera, Lepidoptera, Psocoptera, Diptera, and Blattodea). In particular, this review collected and summarized information regarding the lower development thresholds, lower population thresholds, lower acoustic or respiratory thresholds, lower walking and flying thresholds and lower trap capture thresholds for flying and walking arthropods. The average lower development threshold (LDT) differed among orders: the lowest was reported for Acari (6.8 °C) and Diptera (8.1 °C), followed by Lepidoptera (11.3 °C) and Psocoptera (13.8 °C), and the highest was reported for Coleoptera (14 °C) and Blattodea (15 °C). An exclusion-function was established showing the percentage of pest species (n = 112) that were developmentally suppressed (excluded) due to temperatures reaching the LDT in the range of decreasing temperatures from 25 °C to 0 °C. We scaled various temperature thresholds from the lowest to highest temperature as follows: the walking threshold, the trap capture threshold for walking insects, the lower development threshold, lower population threshold, lower flying threshold and the lower trap capture threshold for flying pests. Important pest species were identified for which information regarding the lower temperature threshold is missing, or for which the information is too variable and should be refined in future research.
Keywords: individual; walking; respiration; populations; flying; thresholds; development; pest management; temperature; forensic entomology